The Effectiveness of BTQ Training on Qur'an Reading Skills on the Spiritual Quotient (SQ) of UINSA Psychology Students - Muzdalifa, Finka Andriana Permata; Nada, Jinan Nisrina; Qowimah, Sirri Nahzatun; Sholeh, Moh (International Conference on Sustainable Health Promotion, 2023)
Spiritual intelligence is important for every individual to have to be able to facilitate solving problems and have meaningful life value. This study aims to see the effectiveness of Qur'an literacy training on increasing students' spiritual quotient. The method used is One Group Pretest Postest Design with a total of 20 samples. The measuring instrument used is in the form  of multiple choices based on students' cognitive aspects of reading the Qur'an. The results showed that BTQ training in Qur'an reading skills can increase the Spiritual Quotient for UINSA Psychology students in semester 6 of class G2. It can be concluded that the applied BTQ Training increases the level of spiritual intelligence of students.